Specific features and development prospects of the agricultural labor market - Amonov Navrozhkhon Salokhiddin oglu (THE INNOVATION ECONOMY, 2026)
This article provides a detailed analysis of the specific characteristics and development prospects of the agricultural labour market in the Kashkadarya region. The study is based on recent Presidential decrees, Cabinet of Ministers’ resolutions, and official data from the Ministry of Labour and the Ministry of Agriculture of Uzbekistan. The analysis identified major challenges such as the high seasonality of agricultural employment, the widespread presence of informal labour, and the shortage of skilled workers caused by migration. The results indicate that in order to ensure sustainable development of the agricultural labour market, several measures are essential: accelerating technological modernisation, reforming vocational education, increasing the participation of youth and women in the labour market, and making efficient use of regional resources. These steps can stabilise agricultural employment in Kashkadarya, raise household incomes, and improve labour productivity